2006
DOI: 10.1128/iai.74.5.2906-2916.2006
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Shiga Toxin-Producing Escherichia coli Bacteria Mitigate Bovine Leukemia Virus Infection in Experimentally Infected Sheep

Abstract: Ruminants often carry gastrointestinal Shiga toxin (Stx)-producing Escherichia coli (STEC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 52 publications
3
13
0
1
Order By: Relevance
“…Stx1 can kill human melanoma cells (Cheung et al 2010) and can remove contaminated tumor cells in stem cell graft (LaCasse et al 1999). Stx1 has antiviral activity (Ferens et al 2007, 2006; Ferens and Hovde 2007, 2000), as has been reported for PAP and TCS (Parikh and Tumer 2004). In contrast, RTA is not antiviral even though it has the same enzymatic activity as the antiviral RIPs (Parikh and Tumer 2004).…”
Section: Discussionsupporting
confidence: 70%
“…Stx1 can kill human melanoma cells (Cheung et al 2010) and can remove contaminated tumor cells in stem cell graft (LaCasse et al 1999). Stx1 has antiviral activity (Ferens et al 2007, 2006; Ferens and Hovde 2007, 2000), as has been reported for PAP and TCS (Parikh and Tumer 2004). In contrast, RTA is not antiviral even though it has the same enzymatic activity as the antiviral RIPs (Parikh and Tumer 2004).…”
Section: Discussionsupporting
confidence: 70%
“…23,24) Even cytosolic expression of the DT-A fragment mediated by a baculovirus gene therapy vector inhibited the proliferation of malignant glioma cells. 25) Furthermore, the A1 fragment has been found to exert antiviral effects on various ruminant viruses such as bovine leukemia virus (BLV), bovine retroviruses, and bovine immunodeficiency virus (BIV), [26][27][28][29] similarly to its inhibitory effects on baculoviruses, observed in the present study. Therefore, considering the strong cytotoxic and antiviral effects of the A1 fragment when it is expressed cytosolically, it appears that this bacterial toxin can be used in gene and antiviral therapy applications.…”
Section: Discussionsupporting
confidence: 50%
“…Phylogenetic comparisons of different strains, using the pol gene as a reference, indicate that BLV and primate T-lymphotropic viruses (PTLV) sequences differ by 42 % [64]; thus BLV forms a distinct clade amongst retroviruses. Within the BLV subgroup, the sequence divergence was below 6% in pol and env indicating a high degree of conservation among different geographical strains [24,25,65-67]. Although the reasons are unknown, this genomic stability might result from a higher fidelity of reverse transcription or from strict replication constraints.…”
Section: The Blv Genomementioning
confidence: 99%